The Effect of Active Smoking of Pregnant Women on Premature Birth: A Meta Analysis - Arifian, Imam Setya; Widyaningsih, Vitri; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Smoking is a well-known major risk factor for premature death from cancer, cardiovascular disease, and chronic obstructive pulmonary disease. When a pregnant woman smokes, she puts herself and her baby at risk. This is because the developing fetus / baby in the mother's womb is in contact with the mother's bloodstream. Any chemical that the mother inhales or swallows can affect the fetus. This study aims to analyze the magnitude of the effect of active smoking on pregnant women with preterm labor by means of a meta-analysis study.Subjects and Method: This was a systematic review and meta-analysis carried out by follow